Social anxiety in adolescents and young adults : translating developmental science into practice - Alfano, Candice A.; Beidel, Deborah C. (American Psychological Association, 2011)
"The concept of social fear dates back to the time of Hippocrates, and the existence of a condition characterized by excessive shyness, social withdrawal, and symptoms of autonomic arousal has long been noted in the psychiatric literature. Although the specific constellation of symptoms that defines this condition has remained largely consistent over the course of more than 100 years, current understanding of the mechanisms that underlie social neurosis has evolved significantly. Today, social anxiety disorder (SAD) affects up to 15% of children, adolescents, and adults (Ruscio et al, 2008; Wittchen, Stein, & Kessler, 1999). Although SAD exists across the life span, the average age of onset is during mid-adolescence; it commonly remains undiagnosed until late adolescence or early adulthood. What is it, then, about this particular developmental stage that seems to be the critical period for onset of this debilitating disorder? This question represents the central query of this book. Although several other volumes have described the etiology, presentation, and treatment of SAD, most have limited their focus to adults, with little more than simple reference to the fact that the disorder is most likely to begin during the teenage years. Because the vast majority of research to date has been conducted among socially anxious adults, such decisions were most certainly reasonable. Within the past decade, however, research has expanded not only to include social anxiety in adolescents and young adults but in many cases to focus exclusively on this age group. The result is an ever-growing body of developmental research in need of both integration and clinical interpretation. The material in this book is, therefore, aimed at researchers and clinicians alike because both groups are confronted with the challenge of keeping abreast of these emergent findings"--Introduction. (PsycINFO Database Record (c) 2011 APA, all rights reserved).